INITIAL MINERAL COMPOSITION OF THE ULTRAMAFIC ROCKS OF SOUTH BELOZYORSKY MASSIF AND DISTRIBUTION OF PRECIOUS METALS - ILVYTSKY, M.; DUDNIK, N.; POPOVCHENKO, S.; SHUKILO, L.; RUZINA, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Having been restored the initial mineral contains ultramafits of Yuzno-Belozersky massive on relicts of primary magmatic mineral and distribution in the cut of ultramafits of noble metals.